2011
DOI: 10.1186/1471-2377-11-135
|View full text |Cite
|
Sign up to set email alerts
|

Supraorbital transcutaneous neurostimulation has sedative effects in healthy subjects

Abstract: BackgroundTranscutaneous neurostimulation (TNS) at extracephalic sites is a well known treatment of pain. Thanks to recent technical progress, the Cefaly® device now also allows supraorbital TNS. During observational clinical studies, several patients reported decreased vigilance or even sleepiness during a session of supraorbital TNS. We decided therefore to explore in more detail the potential sedative effect of supraorbital TNS, using standardized psychophysical tests in healthy volunteers.MethodsWe perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…In addition to the indirect effects on the lateral reticular formation, TNS can also modulate the activity of interneurons in the lateral tegmental field. This is suggested by the sedative effects described during SON stimulation (Piquet et al 2011) which aligns with the relaxing effects following ION stimulation in our subjects. It has been shown that the level of arousal influences in a different manner the early and late components of the BR (Shahani 1968).…”
Section: Effects Of Tns On Brainstem Excitabilitysupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to the indirect effects on the lateral reticular formation, TNS can also modulate the activity of interneurons in the lateral tegmental field. This is suggested by the sedative effects described during SON stimulation (Piquet et al 2011) which aligns with the relaxing effects following ION stimulation in our subjects. It has been shown that the level of arousal influences in a different manner the early and late components of the BR (Shahani 1968).…”
Section: Effects Of Tns On Brainstem Excitabilitysupporting
confidence: 64%
“…In the present study, a short-lasting TNS rather than a chronic TNS was delivered since our aim was to investigate the site of action, cortical and/or subcortical, of the TNS rather than exploring its clinical effects in the short-term period. However, 20-min TNS have been also proved to be able to induce short-term effects in patients with migraine (Piquet et al 2011;Schoenen et al 2013).…”
Section: Effects Of Tns On Cortical Excitability and Sensorimotor Intmentioning
confidence: 99%
“…Based on what has been stated above and considering that no effect was produced on the BR by the sham-TNS, it is likely that the inhibitory effect observed on the R2 component of the BR after TNS is a true TNSinduced aftereffect. It cannot be completely excluded that a TNS-induced reduction in the alertness (Piquet et al 2011;Mercante et al 2015) could be responsible, at least in part, for the prolonged depression of the BR observed following TNS. In our experimental setup, a confounding unspecific effect of sleepiness was minimized asking the subjects to stay relaxed but alert for the whole duration of both real-and sham-TNS experiments, which were then possibly affected by a similar level of sleepiness or boredom.…”
Section: Effects Of Tns On Br Excitabilitymentioning
confidence: 90%
“…By contrast, specific changes in the arousal state induced by the real-TNS seems a plausible mechanism according to the evidence that TNS acts on brain stem nuclei deeply involved in the control of the arousal/sleeping state, such as the ascending reticular system and the locus coeruleus (LC) (Halliday 2004;Samuels and Szabadi 2008). However, our experimental setup was not suitable to measure any TNS effect on the arousal state since the electrical stimulation of the SON, like that of other peripheral nerves, has been reported to induce an increase rather than a decrease in the arousal level (Kwon et al 2000;Piquet et al 2011).…”
Section: Effects Of Tns On Br Excitabilitymentioning
confidence: 97%
“…The 1 st indication for a central effect of the Cefaly ® came from a double-blinded, cross-over, sham-controlled trial in 30 healthy volunteers that assessed its effects on psychomotor tests (43). This study found that reaction time in a psychomotor vigilance task and score on the Fatigue Visual Numeric Scale were significantly increased after one 20 min session of eTNS at 120Hz, while critical flicker fusion frequency was decreased, which suggested that the device had produced a mild, transient sedative effect.…”
Section: Supra-segmental Mechanismsmentioning
confidence: 99%